Wnt5a Promotes Lysosomal Cholesterol Egress and Protects Against Atherosclerosis. Issue 2 (21st January 2022) - Awan, Sara; Lambert, Magalie; Imtiaz, Ali; Alpy, Fabien; Tomasetto, Catherine; Oulad-Abdelghani, Mustapha; Schaeffer, Christine; Moritz, Chloé; Julien-David, Diane; Najib, Souad; Martinez, Laurent O.; Matz, Rachel L.; et al.
Abstract : Background: Impairment of cellular cholesterol trafficking is at the heart of atherosclerotic lesions formation. This involves egress of cholesterol from the lysosomes and 2 lysosomal proteins, the NPC1 (Niemann–Pick C1) and NPC2 that promotes cholesterol trafficking. However, movement of cholesterol out the lysosome and how disrupted cholesterol trafficking leads to atherosclerosis is unclear. As the Wnt ligand, Wnt5a inhibits the intracellular accumulation of cholesterol in multiple cell types, we tested whether Wnt5a interacts with the lysosomal cholesterol export machinery and studied its role in atherosclerotic lesions formation. Methods: We generated mice deleted for the Wnt5a gene in vascular smooth muscle cells. To establish whether Wnt5a also protects against cholesterol accumulation in human vascular smooth muscle cells, we used a CRISPR/Cas9 guided nuclease approach to generate human vascular smooth muscle cells knockout for Wnt5a. Results: We show that Wnt5a is a crucial component of the lysosomal cholesterol export machinery. By increasing lysosomal acid lipase expression, decreasing metabolic signaling by the mTORC1 (mechanistic target of rapamycin complex 1) kinase, and through binding to NPC1 and NPC2, Wnt5a senses changes in dietary cholesterol supply and promotes lysosomal cholesterol egress to the endoplasmic reticulum. Consequently, loss of Wnt5a decoupled mTORC1 from variations in lysosomal sterol levels, disrupted lysosomal function, decreased cholesterol content in the endoplasmic reticulum, and promoted atherosclerosis. Conclusions: These results reveal an unexpected function of the Wnt5a pathway as essential for maintaining cholesterol homeostasis in vivo. Abstract : Supplemental Digital Content is available in the text.